Eribulin mesylate reduces tumor microenvironment abnormality by vascular remodeling in preclinical human breast cancer models. Issue 10 (16th September 2014) - Funahashi, Yasuhiro; Okamoto, Kiyoshi; Adachi, Yusuke; Semba, Taro; Uesugi, Mai; Ozawa, Yoichi; Tohyama, Osamu; Uehara, Taisuke; Kimura, Takayuki; Watanabe, Hideki; Asano, Makoto; Kawano, Satoshi; et al.
<x xml:space="preserve">Abstract</x> Eribulin mesylate is a synthetic macrocyclic ketone analog of the marine sponge natural product halichondrin B and an inhibitor of microtubule dynamics. Some tubulin‐binding drugs are known to have antivascular (antiangiogenesis or vascular‐disrupting) activities that can target abnormal tumor vessels. Using dynamic contrast‐enhanced MRI analyses, here we show that eribulin induces remodeling of tumor vasculature through a novel antivascular activity in MX‐1 and MDA‐MB‐231 human breast cancer xenograft models. Vascular remodeling associated with improved perfusion was shown by Hoechst 33342 staining and by increased microvessel density together with decreased mean vascular areas and fewer branched vessels in tumor tissues, as determined by immunohistochemical staining for endothelial marker CD31. Quantitative RT‐PCR analysis of normal host cells in the stroma of xenograft tumors showed that eribulin altered the expression of mouse (host) genes in angiogenesis signaling pathways controlling endothelial cell–pericyte interactions, and in the epithelial–mesenchymal transition pathway in the context of the tumor microenvironment. Eribulin also decreased hypoxia‐associated protein expression of mouse (host) vascular endothelial growth factor by ELISA and human CA9 by immunohistochemical analysis. Prior treatment with eribulin enhanced the anti‐tumor activity of capecitabine in the MDA‐MB‐231 xenograft model. These findings suggest that eribulin‐induced remodeling of abnormal tumor vasculature leads to a more functional microenvironment that may reduce the aggressiveness of tumors due to elimination of inner tumor hypoxia. Because abnormal tumor microenvironments enhance both drug resistance and metastasis, the apparent ability of eribulin to reverse these aggressive characteristics may contribute to its clinical benefits.